LEGAL FORCE OF INHERITANCE CERTIFICATES ISSUED BY THE VILLAGE HEAD AS THE BASIS FOR OBTAINING THE OWNERSHIP RIGHT TO LAND (IN BLIMBINGSARI VILLAGE, JEMBRANA REGENCY, BALI PROVINCE) - Ni Putu Theresa Putri Nusantara; I Made Suwitra; I Nyoman Sujana (NOTARIIL Jurnal Kenotariatan, 2021)
This study examines the existence of the Bali customary law for the transfer of land rights in Blimbingsari Village, and examines function of the Inheritance Certificate for the transfer of rights to land through inheritance. The research method used in this study is an empirical law research. In this case the research uses empirical legal research conducted in Blimbingsari Village, Jembrana Regency. The results showed that the inheritance law that applies to Christian Balinese tribes in Blimbingsari Village, Jembrana, Bali is receptive to Balinese customary inheritance laws which should only be used for Hindus. In its implementation, it is not the Hindu religious law that was received by the Blimbingsari Village community but the Balinese customary inheritance law that was received. Moreover, legal force of a Certificate of Inheritance issued by the village head for the Christian Balinese community in Blimbingsari Village, Jembrana, Bali can be used as a basis in the transfer of ownership rights to the land for the heirs.